2021
DOI: 10.17762/turcomat.v12i3.1075
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual Framework of Kxpert:Knowledge-Based Information Retrieval for Expert Profiling

Abstract: With the constant demand for expertise within organisation, especially in boosting the credibility of experts in the organisation, it is a need to bring forth a simple yet effective knowledge-based expert profiling based on information retrieved from credential publication sites.  A number of frameworks from previous authors are analysed to propose one sound framework for a case university, to improve its existing research expert database, to make it more efficient in the information retrieval process and know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Turnover-induced knowledge loss has been reported in previous research, especially in organisations managing software development projects (Rigby et al, 2016;Nassif & Robillard, 2017) and in knowledge-intensive institutions (Ismail & Suhaimi, 2021;Ismail, 2016). Before one could understand the knowledge loss and knowledge recovery, it is important to realise that knowledge continuity is highly significant for an organisation.…”
Section: Knowledge Loss and Recoverymentioning
confidence: 80%
See 2 more Smart Citations
“…Turnover-induced knowledge loss has been reported in previous research, especially in organisations managing software development projects (Rigby et al, 2016;Nassif & Robillard, 2017) and in knowledge-intensive institutions (Ismail & Suhaimi, 2021;Ismail, 2016). Before one could understand the knowledge loss and knowledge recovery, it is important to realise that knowledge continuity is highly significant for an organisation.…”
Section: Knowledge Loss and Recoverymentioning
confidence: 80%
“…Technically, it is found that intelligent software agents could be useful for knowledge recovery and mitigating knowledge loss (Ismail & Suhaimi, 2021;Ismail, 2016). This technical domain has expanded into the concept of Agent of Things (AoT), derived from the popular domain of Internet of Things (IoT), but focusing on the intelligent software developed within the environment where the software agent sits.…”
Section: Intelligent Software Agents In Knowledge Managementmentioning
confidence: 99%
See 1 more Smart Citation